Pengaruh Kepemilikan Manajerial, Profitabilitas, Leverage, dan Ukuran Perusahaan Terhadap Kebijakan Dividen pada Perusahaan Sektor Makanan dan Minuman yang Terdaftar di BEI Tahun 2019-2023 - Nafis, Moh. Abi Adhurun; Widiawati, Hestin Sri; Linawati, Linawati (FEB Universitas Maritim Semarang, 2025)
The Dividend Payout Ratio (DPR) changes in food and beverage companies listed on the Indonesia Stock Exchange between 2019 and 2023, which reflect shifts in dividend policy, are what spurred this study. Dividend policy is important since it helps to win over investors. Nonetheless, management frequently has to decide whether to pay dividends or keep profits for investments. Finding out how management ownership, profitability, leverage, and business size affect dividend policy in food and beverage companies listed on the Indonesia Stock Exchange is the aim of this study. This study is classified as a quantitative causality study. 50 food and beverage firms made up the sample, which was selected using a purposive sampling technique. The SPSS version 25 multiple linear regression software was used to examine these data. This study demonstrates that the dividend policy of companies in the food and beverage sector listed on the Indonesia Stock Exchange is influenced, in part, by management ownership, profitability, leverage, and company size. Conversely, the dividend policy of companies in the food and beverage sector listed on the Indonesia Stock Exchange is influenced by management ownership, profitability, leverage, and company size.